Effects of Deceptive Advertising on Consumer Loyalty in Telecommunication Industry of Pakistan - Hasan, Syed Akif; Subhani, Muhammad Imtiaz; Mateen, Ana (Information Management and Business Review, 2011)
This study is an attempt to interrogate the effects of deceptive advertising on consumer loyalty in telecommunication industry of Pakistan. Four variables, Call Charges (CC), Network Coverage (NC), Network Quality (NQ) and Customer Service (CS) were used to measure deception in Telecom Ads and then its effect on consumer loyalty while the consumer preference is used as the proxy of consumer loyalty. 10,000 random individuals from telecom industry were selected to conclude the results. Testing specification confirmed that the deception overwhelmingly exists in telecom ads and none of the telecom companies were providing exactly the same quality of service in terms of Call Charges, Network Coverage, Network Quality and Customer Service, as they promise in their advertisements, while, the consumers are inclined towards the services where the deceptions are seemingly meager.